Does Family Cohesion Predict Children's Effort? The Mediating Roles of Sense of Coherence, Hope, and Loneliness. Issue 5 (4th July 2018) - Feldman, David B.; Einav, Michal; Margalit, Malka
ABSTRACT: The degree of cohesion and support within families has often been considered a predictor of students' effort-investment and success in school. The objectives of this study are to examine the roles of personal factors (i.e., sense of coherence and hopeful thinking) as well as interpersonal factors (i.e., loneliness) in mediating the relationship between family cohesion and effort. The sample consists of 1719 elementary school children (781 boys and 938 girls) from the fifth and six grades (mean age = 10.25, SD = 0.70) of 29 elementary schools in central Israel. Students answered study questionnaires in the middle of their academic year. Analyses utilizing hierarchical multiple regression and Hayes' bootstrapping approach (PROCESS; Preacher & Hayes, 2008) were used. The results support the distinctive contribution of family cohesion and the mediating roles of sense of coherence and hope (as protective factors) as well as loneliness (as a risk factor) in predicting students' school effort. This study has important educational implications, emphasizing the value of promoting hopeful thinking and coping with loneliness in helping students to thrive in their studies.